Blockchain-Driven Cybersecurity Framework for Smart Digital Ecosystems - Marion Kayla; Crispinus Ode; Marion Sanaipei (Eastasouth Institute, 2026)
The rapid growth of smart digital environments, driven by cloud computing, the Internet of Things (IoT), artificial intelligence (AI), and interconnected cyber-physical systems, has significantly increased the frequency and sophistication of cyber threats. Conventional cybersecurity approaches often struggle to ensure data integrity, trust, and resilience in decentralized and highly dynamic environments, highlighting the need for more robust security frameworks. This review paper examines the role of blockchain technology in enhancing cybersecurity for smart digital ecosystems through decentralized authentication, immutable data storage, secure information sharing, and intelligent threat mitigation. The study reviews blockchain architectures, consensus mechanisms, security protocols, and their integration with emerging technologies such as AI, machine learning, edge computing, and cloud platforms. A comparative analysis of consensus algorithms, including Proof of Work (PoW), Proof of Stake (PoS), and Practical Byzantine Fault Tolerance (PBFT), is presented to evaluate their effectiveness in improving data integrity, scalability, and security. The review further analyzes hybrid blockchain-AI cybersecurity frameworks, demonstrating that integrating blockchain with AI-based intrusion detection systems significantly improves threat detection accuracy, reduces successful cyberattacks, and enhances system resilience. The paper also discusses major implementation challenges, including scalability, computational overhead, interoperability, energy consumption, and privacy preservation, which continue to hinder large-scale deployment. Finally, future research directions are identified, emphasizing explainable artificial intelligence (XAI), federated learning, zero-trust architectures, edge intelligence, and privacy-preserving blockchain solutions to strengthen next-generation cybersecurity systems. Overall, this review demonstrates that blockchain-based cybersecurity frameworks provide a secure, transparent, and resilient foundation for protecting smart digital environments against increasingly sophisticated cyber threats while supporting trustworthy and scalable digital transformation.